THE CHALLENGES OF MAINTAINING ORAL HEALTH IN HEPATITIS C - Cristina Raluca Iorga; Ana Magdalena Bratu; Razvan Leata; Mariana Ilie; Adrian Petru Radu; Gabi Topor; Camelia Ana Grigore (Romanian Society of Oral Rehabilitation, 2023)
Hepatitis C is a global health problem, affecting millions of people and having significant implications for the whole organism. In this context, attention to oral health among people with hepatitis C is becoming increasingly important. Hepatitis C is a chronic viral infection of the liver, transmitted mainly by contact with infected blood, and its treatment involves the use of strong antiviral drugs. However, these treatments can have side effects and influence the oral health of patients. Adopting a regular oral hygiene regimen, including dental brushing, flossing and mouthwash, is an essential component in maintaining oral health for people with hepatitis C. Schedule regular visits to the dentist for dental exams and professional cleanings contributes to the early identification of oral problems and the prevention of complications.People undergoing treatment for hepatitis C should be aware of possible side effects, such as dry mouth, and take appropriate measures to manage these symptoms.